Analysis of Price and Healthy Food Packaging Information on Purchasing Behavior through Customer Satisfaction - Nuzul Inas Nabila; Aida Sari; Risda Marvinita; Tazkiyah Sakinah; Nyimas Latifah Azzahra (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study analyses the effect of price and product information on healthy food packaging on consumer purchasing behaviour, with customer satisfaction as a mediating variable. Changes in consumer behaviour are triggered by easy access to information, increased awareness of quality of life, and social and cultural factors. Using a quantitative approach with PLS analysis, this study involved healthy food consumers as respondents. The results show that price and packaging information have a significant impact on purchasing behaviour, both directly and through their effect on customer satisfaction. These findings emphasise the importance of product communication strategies and appropriate pricing to increase satisfaction and encourage purchasing decisions in an increasingly competitive healthy food market.